From 2013 to Merdeka: Investigating Curriculum Change and Its Impact on Students’ Motivation in Learning English - Setyowati (TEKILA: Journal of Language Teaching and Literature, 2025)
This qualitative case study investigates the impact of the curriculum transition from the 2013 Curriculum to the Merdeka Curriculum on students’ motivation in learning English at SMP YPK Fakfak. The study involved 80 students across grades VII to IX, with grades VII and VIII learning under the Merdeka Curriculum and grade IX under the 2013 Curriculum. Data were collected using two main instruments: a motivation questionnaire and semi-structured interviews. The questionnaire assessed students’ motivation levels, while the interviews explored personal experiences and influencing factors in greater depth. The findings revealed that students taught under the Merdeka Curriculum consistently demonstrated very high levels of motivation, with scores ranging from 92.05 to 96.01. In contrast, students under the 2013 Curriculum showed slightly lower motivation, with scores between 80.47 and 82.04. Key internal factors contributing to motivation included personal interest, desire to communicate in English, and enjoyment of interactive classroom activities. External factors such as parental support, access to learning media, and school facilities also played a significant role. Students under the Merdeka Curriculum expressed greater enjoyment and engagement due to diverse and creative learning activities such as drama, videos, and songs, which helped boost their confidence and reduce anxiety. Meanwhile, the exam-focused and rigid structure of the 2013 Curriculum was perceived as limiting student interest and participation. The study concludes that the Merdeka Curriculum’s flexible, student-centered design positively influences learners’ motivation in English learning. It highlights the value of interactive media, teacher encouragement, and a supportive learning environment in enhancing student engagement.